2017
DOI: 10.18805/ijar.v0iof.7005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different genetic and non-genetic factors on Pre weaninglitter and growth performance of pigs

Abstract: The study was carried out on two different genetic groups of pig viz. Duroc and Hampshire maintained at pig breeding farm of National Research Centre on Pig, Guwahati. Effect of different genetic group and non-genetic factors (year and season of farrowing and parity) were estimated by least squares analysis of variance for different litter production, weight and pre weaning growth rate. Genetic group and parity revealed highly significant (P<0.01) effect on all the traits under study. However, effect of year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
2
0
1
Order By: Relevance
“…Similarly, Goshu and Singh (2013) also reported that the effects of season on mortality rates in Holstein Friesian females from birth to age at first calving were found to be non-significant, while year differences were found to be highly significant (P <0.01). Similar findings were also reported by Upadhyay et al (2017) for Karan Fries; Banik and Naskar (2006) and Abbas (2005) for Sahiwal as the period of birth was found highly significant (P<0.01) while season of birth and parity had non-significant effect on mortality. Regarding replacement rate, Thiruvenkadan and Devendran (2014) also reported the significant effect of period of birth on replacement rate in Murrah buffalo.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly, Goshu and Singh (2013) also reported that the effects of season on mortality rates in Holstein Friesian females from birth to age at first calving were found to be non-significant, while year differences were found to be highly significant (P <0.01). Similar findings were also reported by Upadhyay et al (2017) for Karan Fries; Banik and Naskar (2006) and Abbas (2005) for Sahiwal as the period of birth was found highly significant (P<0.01) while season of birth and parity had non-significant effect on mortality. Regarding replacement rate, Thiruvenkadan and Devendran (2014) also reported the significant effect of period of birth on replacement rate in Murrah buffalo.…”
Section: Resultssupporting
confidence: 87%
“…Disposal, mortality, culling and replacement rate: The overall incidence of disposal, mortality and culling was 27.35, 23.63 and 3.72% respectively, while replacement rate on female calves and total calves basis were 72.64 and 37.55% respectively, upto age at first calving (Table 1). Almost similar findings of mortality upto AFC were reported by Upadhyay et al (2014) and Abbas (2005) for Sahiwal while lower estimates were observed by Shahi and Kumar (2006), Tomar and Rawal (1994) for Sahiwal; Lathwal et al (1993) for Red Sindhi and higher values were reported by Banik and Naskar (2006) There was significant effect (P<0.01) of period of birth and birth weight of calf on the disposal, mortality and replacement rate of calves upto age at first calving. The effect of period might be due to changes in different management strategies and practices over the period as it was higher in first period (P1) and lower in third period (P3) for disposal and mortality, while replacement rate was higher during third period (P3).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation